Can the EU ETS and its revenues tackle the impact of high carbon prices? - Simone Borghesi; Albert Ferrari (EconPol Forum, 2023)
The EU ETS with companion policies is more robust than relying solely on either regulatory or carbon-pricing interventions. Policies should be developed to account for the disparate impacts of the EU ETS across firms and regions. Acceptability of carbon pricing depends on how the carbon price is communicated and revenues used. The EU ETS revenues might decrease at higher carbon prices following a carbon Laffer curve. Beyond revenues, policymakers may have to consider additional sources for funding distributional compensations in the long run.
Keywords: 330